The Effect of Learning Independence and Gender on Students’ Mathematics Learning Achievement - Imron Farhani, Muhammad Andi; Noor, Naili Lumaati (Universitas Islam Negeri Sunan Kudus, 2024)
This study was conducted at MTs Maslakul Huda Sluke Rembang, emphasizing the importance of self-directed learning and gender in mathematics achievement. The objectives of this study were to determine 1) the significant influence of self-directed learning on mathematics achievement, 2) the significant influence of gender on mathematics achievement, and 3) the significant interaction between self-directed learning and gender on mathematics achievement. This study used a quantitative approach with a correlational method. The research sample was randomly selected and consisted of 37 eighth-grade students from MTs Maslakul Huda Sluke Rembang. Data were collected through tests and questionnaires, using a self-directed learning questionnaire, gender data, and a mathematics achievement test. Hypothesis testing was conducted using two-way ANOVA and Tukey's post-hoc test. The results showed a significant influence of self-directed learning on mathematics achievement with a significance value of 0,000<0,05. Tukey's post-hoc test indicated a significance value among the self-directed learning groups of 0,000, showing significant differences among the groups. There was no significant difference between gender and mathematics achievement with a significance value of 0,121>0,05. There was a significant interaction between self-directed learning and gender on mathematics achievement with a significance value of 0,016<0,05. The implications of this study are the importance of enhancing students' self-directed learning as a key factor in improving mathematics achievement and that gender does not significantly affect this, so the focus of learning can be more directed towards developing students' self-directed learning while still considering gender equality to enhance mathematics achievement. Penelitian ini dilakukan di MTs Maslakul Huda Sluke Rembang dengan menekankan pentingnya kemandirian belajar dan gender dalam prestasi belajar matematika. Tujuan penelitian ini adalah untuk mengetahui 1) pengaruh signifikan kemandirian belajar terhadap prestasi belajar matematika, 2) pengaruh signifikan antara gender terhadap prestasi belajar matematika, 3) pengaruh interaksi signifikan antara kemandirian belajar dan gender terhadap prestasi belajar matematika. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Sampel penelitian dipilih secara acak dan terdiri dari 37 siswa kelas VIII A MTs Maslakul Huda Sluke Rembang. Data dikumpulkan melalui tes dan angket, menggunakan instrumen angket kemandirian belajar, data gender, dan tes prestasi belajar matematika. Pengujian hipotesis dilakukan dengan uji two-way ANOVA dan uji lanjut tukey. Hasil penelitian menunjukkan terdapat pengaruh signifikan antara kemandirian belajar terhadap prestasi belajar matematika dengan nilai Sig sebesar 0,000<0,05. Uji lanjut tukey menunjukkan nilai signifikansi antar kelompok kemandirian belajar sebesar 0,000, menunjukkan perbedaan signifikan antar kelompok. Tidak terdapat perbedaan signifikan antara gender terhadap prestasi belajar matematika dengan nilai Sig sebesar 0,121>0,05. Terdapat interaksi signifikan antara kemandirian belajar dan gender terhadap prestasi belajar matematika dengan nilai Sig sebesar 0,016<0,05. Implikasi dari penelitian ini adalah pentingnya peningkatan kemandirian belajar siswa sebagai faktor utama dalam meningkatkan prestasi belajar matematika, serta bahwa faktor gender tidak mempengaruhi secara signifikan, sehingga fokus pembelajaran dapat lebih diarahkan pada pengembangan kemandirian belajar siswa dengan tetap memperhatikan kesetaraan gender agar meningkatkan prestasi belajar matematika.